COMPARISON OF THE EFFECT OF LOW BACK PAIN ON THEIR DAILY LIFE ACTIVITIES IN SEDENTARY WOMEN AND MOTHERS WITH PHYSICALLY HANDICAPPED CHILDREN - TARAKCI, DEVRİM; YELDAN, İPEK; Zengin, Ayse; Tekeoglu, Anil; KOSTANOĞLU, ALİS; KOSTANOĞLU, ALİS; Kuru, Tugba; AKBABA, YILDIZ (My University, 2010)
Objective The aim of our study was to make a comparison on how much low back pain complaints of mothers with physically handicapped children and sedentary women restrict their daily life activities